Development of a Framework for Generating Driving Safety Assessment Scenarios for Automated Vehicles - Ko, Woori; Park, Sangmin; Yun, Jaewoong; Park, Sungho; Yun, Ilsoo (Sensors, 2022)
Despite the technological advances in automated driving systems, traffic accidents involving automated vehicles (AVs) continue to occur, raising concerns over the safety and reliability of automated driving. For the smooth commercialization of AVs, it is necessary to systematically assess the driving safety of AVs under the various situations that they potentially face. In this context, these various situations are mostly implemented by using systematically developed scenarios. In accordance with this need, a scenario generation framework for the assessment of the driving safety of AVs is proposed by this study. The proposed framework provides a unified form of assessment with key components for each scenario stage to facilitate systematization and objectivity. The performance of the driving safety assessment scenarios generated within the proposed framework was verified. Traffic accident report data were used for verification, and the usefulness of the proposed framework was confirmed by generating a set of scenarios, ranging from functional scenarios to test cases. The scenario generation framework proposed in this study can be used to provide sustainable scenarios. In addition, from this, it is possible to create assessment scenarios for all road types and various assessment spaces, such as simulations, proving grounds, and real roads.
Keywords: Assessment; Automated driving; Automated driving systems; Automated vehicles; Driving safety; Framework; Safety assessments; Scenario; Scenarios generation; Technological advances; Accidents, Traffic; Automation; Automobile Driving; Autonomous Vehicles; Reproducibility of Results; Safety; assessment; automated vehicles; driving safety; framework; scenarios